Representações sobre ensino-aprendizagem de língua inglesa de alunos de uma 5ª série do ensino fundamental - Nunes, Camila Matos Venesiano (2008)
This dissertation aims at finding out what representations 5th grade students in a public school have on learning English. This research relies on the PCN-LE (National Curricular Parameters for Foreign Languages, 1998) as a guide and documental source on learning- teaching English in Brazilian schools. For the data analysis, it is based on the theories of Vygoksky (2007 in the last consulted version), on the role of language according to Bakhtin (2006 in the last consulted version), and on the idea of social representations according to Moscovici (2005) and Jodelet (2001). The methodological approach used is a case study, according to Nunan (1992). The context of this research is a state school located in the Great São Paulo area; the participants are the teacher-researcher and 5 students between 10 and 11 years of age. The results reveal that students wish to learn English in order to travel, to live abroad and mainly to work, but that they do not study the language because of a real interest in the culture of the countries where English is the mother tongue. In the teaching-learning EFL process at school such perceptions show that English is seen as of immediate and utilitarian use. The social representations of the students that took part in the research show the reasons why this occurs